Procurement Process Analysis Using Process Mining in Cement Manufacturing Company (Case Study PT. Semen Indonesia Persero, Tbk) - Dharmawan, Yogantara Setya; Izatri, Dini Idzni; Rohmah, Nofita Idaroka (Institut Teknologi Sepuluh Nopember, 2020)
Procurement process holds crucial role in companiesâ€™ business process, particularly manufacturing company. PT Semen Indonesia as one of manufacturing Companies in Indonesia relies on procurement process in order to fulfill their business. However, existing e-procurement does not cover all the procurement process which creates process variants have made whole procurement process run into bottleneck. Deeper analysis required to dig insights on the process variants to derive the cause of problem. Hence, this research aims to explore Process Mining to gain more insights from the process using data log derived from the system. BPM lifecycle used as an approach to reach the objective of the research. However, not all phases in BPM lifecycle are imposed, yet Process Identification, Process Discovery and Process Analysis. The result showed that top three activities that take time most are Upload to E Procurement, Purchasing Configuration, and Technical Evaluation which require improvements.Â